Double‐sided surface functionalization: An effective approach to stabilize and modulate the electronic structure of graphene‐like borophene. Issue 3 (14th July 2020) - Tang, Xiao; Gu, Jinxing; Shang, Jing; Chen, Zhongfang; Kou, Liangzhi
Abstract: Graphene‐like borophene was theoretically proposed and recently synthesized on Al (111) surface, however, how to conquer its structural instability is still an open question. By means of density functional theory computations, we theoretically predicted that honeycomb borophene can be well stabilized by double‐sided surface passivation with monovalent functional groups (X = F, Cl, Br, I, OH, and NH2 ) due to the electron redistributions. The system undergoes the transition from metallic to semiconducting upon functionalization, while the energy gap depends on the choice of functional groups. Under external strain, the gap values can be manipulated over a broad range. Our further calculations indicated that the functionalized borophene possesses moderate and anisotropic carrier mobility, which is comparable to or even higher than some 2D materials such as MoS2 and phosphorene. Our work provides a feasible strategy to effectively stabilize the graphene‐like borophene and tune the electronic properties with great potentials for electronic applications. Double‐sized functionalization by monovalent functional groups (F, Cl, Br, I, OH, and NH2 ) is predicted to be an effective and feasible way to stabilize the graphene‐like borophene and modulate the electronic properties. The functionalized borophenes are semiconductors with a wide range of gaps, which can be further tuned by external strains, thus are promising for various nanoelectronics applications. Abstract : Double‐sized functionalization by monovalent functional groups (F, Cl, Br, I, OH, and NH2 ) is predicted to be an effective and feasible way to stabilize the graphene‐like borophene and modulate the electronic properties. The functionalized borophenes are semiconductors with a wide range of gaps, which can be further tuned by external strains, thus are promising for various nanoelectronics applications.